Internalisasi Nilai Tolerasi Melalui Modal Sosial di Madrasah - Dita Hendriani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study discusses the internalization of tolerance values ​​through social capital in madrasahs. Using a qualitative approach and case study at MA Futuhiyyah Jeketro, this study examines how social capital in the form of trust, networks, and values ​​can shape a culture of tolerance in the educational environment. The results of the study indicate that public trust in madrasahs, supported by the quality of education and good management of madrasahs, contributes to building a harmonious environment. In addition, social networks between madrasahs and various parties, including parents, communities, and educational organizations, are important factors in strengthening tolerance values. The norms and values ​​applied in madrasahs, such as discipline, honesty, and religiosity, play a role in shaping the character of students who are more inclusive and respect diversity. Thus, the internalization of tolerance values ​​in madrasahs can be strengthened through effective management of social capital, thereby creating a more open and harmonious educational environment.